2019
DOI: 10.1016/j.surfcoat.2019.125068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface adsorption on icing behaviour of metallic coating

Abstract: Icephobicity of materials has received intensive attention in recent years due to the increasing requirement of ice protection in aerospace, wind energy and power lines. However, the influencing factors of material icephobicity have not been well identified. In this work, the effect of surface gaseous adsorption on icing behaviour of materials was investigated for the first time.Ni-Cu-P coatings with different surface morphologies were fabricated and used as the objects of the study. Environmental scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…When the SHS was removed, the water droplets returned to spherical again. It can be seen that the droplet presents Cassie state ( Cassie and Baxter, 1944 ) on the SH solid surface, rather than Wenzel state in wet contact model ( Wang et al., 2019a ).…”
Section: Removing Surface Water Droplets Before Freezingmentioning
confidence: 99%
See 1 more Smart Citation
“…When the SHS was removed, the water droplets returned to spherical again. It can be seen that the droplet presents Cassie state ( Cassie and Baxter, 1944 ) on the SH solid surface, rather than Wenzel state in wet contact model ( Wang et al., 2019a ).…”
Section: Removing Surface Water Droplets Before Freezingmentioning
confidence: 99%
“… Wang et al. (2019a) found that when a droplet hit an SHS, the kinetic energy of the droplet's impact was transferred to the surface energy, enabling the droplet to completely rebound from the surface.…”
Section: Removing Surface Water Droplets Before Freezingmentioning
confidence: 99%
“…The sessile drop technique was used to measure water contact angles (WCAs) using an FTÅ 200 goniometer and 5 ll of a controlled volume of water drop was analysed. The tests were conducted at room temperature, and the measurement method is described elsewhere [24,25]. The static and dynamic water contact angles (WCAs), including advancing WCAs (AWCAs), receding WCAs (RWCAs), and contact angle hysteresis (CAH), are summarised in supplementary Table S1.…”
Section: Evaluation Of Hydrophobicitymentioning
confidence: 99%
“…An extended version of LTM (ELTM) allows the same sample to be reused for later observation or analysis by EDS in a different SEM or ESEM (Tihlaříková et al, 2019). Furthermore, several subzero temperature ESEM studies were performed including mainly dynamic observations such as nucleation processes (Zimmermann et al, 2007(Zimmermann et al, , 2008Varanasi et al, 2010;Wang et al, 2016Wang et al, , 2019, observation of liquid water droplets under triple-point pressure (Chen et al, 2017), observation of uranyl salt brine on the ice surface (Krausko et al, 2014), sublimation of frozen aqueous systems (Yang et al, 2017;Vetráková et al, 2020), ice crystal growth (Pedersen et al, 2011), morphology of ice and liquid brine at various freezing conditions (Vetráková et al, 2019), morphology of nitric acid and water ice films (Keyser & Leu, 1993), control of ice formation (Lo et al, 2017), and sublimation-induced morphology of ice (Nair et al, 2018). Although dynamic experiments of ice-containing samples in ESEM are very appealing, even more challenging is static observation at thermodynamic equilibrium, which would enable the observation of the constant intact morphology of a frozen aqueous sample, and considerably broaden the ESEM observation possibilities.…”
Section: Introductionmentioning
confidence: 99%